ANALYSIS OF THE IMPLEMENTATION OF THE LIVESTOCK GRANT PROGRAM IN EAST LAMPUNG REGENCY (Study at the Livestock Service Office of East Lampung Regency) - Rika Mariyana; Malik Malik (International Journal of Multidisciplinary Reseach, 2026)
The research method used is descriptive qualitative research. This method is used to describe the analysis of the implementation of the Livestock Grant Program in East Lampung Regency (Study at the East Lampung Regency Livestock Service). All data was obtained directly from informants in the field using interviews and document studies. The results of the study indicate that several major obstacles were identified, namely: (a) Communication Dimension: Communication between relevant parties has not been effective, both between the central and regional governments, leaders and implementers, and between the agency and grant recipient groups. (b) Resource Dimension: Limited resources, particularly the number and competence of human resources, operational monitoring budgets, and infrastructure, are the main obstacles. (c) Disposition or Attitude Dimension: Implementer motivation and commitment in the field are still diverse. (d) The hierarchical bureaucratic structure, unstandardized standard operating procedures (SOPs), and lengthy administrative processes hamper the speed of grant disbursement and oversight.